Reexamining the Kuznets Curve: evidence for Brazil in the period 1981-2009 - Tabosa, Francisco Jose Silva (2016)
The present study investigated the hypothesis of the Kuznets Curve in order to check if there is a "U Inverted" relationship between the income inequality and economic growth in Brazil in the period since 1981 to 2009. Through the econometrics of panel data (fixed effects, random effects and first difference), and using the linear form of average household income per capita, as a measure of economic growth, and the Gini and Theil indicators, for the measurement of income inequality, were estimated two models: the usual quadratic form, by Ahluwalia (1976 b), and a modification of the cubic form, by List and Gallet (1999). For a better understanding of the relationship between these two variables, the analysis was divided into three periods. Empirical evidence showed that, in general, the Kuznets hypothesis isn’t corroborated. From a theoretical analysis of the political, economic and social context experienced by Brazil in contemporaneity, it is believed that effective public policies that provide quality in basic social services are essential to avoid a new cycle of rising inequality.